The American Society for Clinical Pathology's Job Satisfaction, Well-Being, and Burnout Survey of Laboratory Professionals. Issue 4 (21st February 2020) - Garcia, Edna; Kundu, Iman; Kelly, Melissa; Soles, Ryan; Mulder, Lotte; Talmon, Geoffrey A
Abstract: Objectives: To examine job satisfaction, well-being, job stress, and burnout among laboratory professionals. Methods: The study utilized a cross-sectional survey design. The survey was administered online via the American Society for Clinical Pathology's survey tool, to elicit information about job satisfaction, well-being, job stress, and burnout among medical laboratory professionals. Results: Although this survey shows high job satisfaction among respondents, overall job-related stress is high and burnout is prevalent. The majority of the respondents rated their work-life balance as "fair." The main contributing factors to job stress, burnout, and work-life balance are quantity of workload and understaffing. Conclusions: Based on the results of this survey, creating targeted interventions may help improve the quality of well-being programs for laboratory professionals. A comprehensive wellness program developed at the institutional, local, and national levels may improve morale and alleviate the recruitment and retention challenges faced by medical laboratory professionals.